What the Digital Millennium Copyright Act Can Learn from Medical Marijuana: Fixing the Antitrafficking Provisions by Basing Liability on the Likelihood of Harm - Agento, Zoe (The Columbia Journal of Law & the Arts, 2012)
This paper addresses the contradiction posed by a law that expressly allows decrypting a DVD to make certain types of fair uses while also banning the software necessary for decryption. Section 1201 of the Digital Millennium Copyright Act allows users to circumvent the digital locks protecting copyrighted works in some circumstances, but prohibits manufacturing and distributing the tools required to do so in all circumstances. In effect, § 1201 grants rights while banning the means necessary to take advantage of those rights. Circumvention tools are indeed capable of causing harm-by unlocking digital works for the purpose of infringement. But circumvention tools are also necessary for valuable uses-making digitally locked works available for purposes of free speech, research, education and privacy. In essence, regulating circumvention tools is the problem of regulating a tool with both fair and foul uses. This is not a new problem. As in legal regulations of similarly dual purpose tools, from medical marijuana to locksmith tools, liability for manufacturing and distributing circumvention tools should be based on the likelihood that such activity actually leads to harm. The example of medical marijuana illustrates how legislative reform allowing limited access would be superior to the current comprehensive ban. Finally, given the improbability of immediate legislative reform, the author proposes a short term, partial solution in the form of a judicial reinterpretation of § 1201.